2009
DOI: 10.1016/j.neuroimage.2009.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Two temporal channels in human V1 identified using fMRI

Abstract: Human visual sensitivity to a fairly broad class of dynamic stimuli can be modeled accurately using two temporal channels. Here, we analyze fMRI measurements of the temporal step response to spatially uniform stimuli to estimate these channels in human primary visual cortex (V1). In agreement with the psychophysical literature, the V1 fMRI temporal responses are modeled accurately as a mixture of two (transient and sustained) channels. We derive estimates of the relative contributions from these two channels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 31 publications
(42 reference statements)
7
52
1
Order By: Relevance
“…Another explanation is that the parafovea may be more sensitive to the rapid flicker of our fluorescent monitor backlight. While some cells in macaque visual cortex can follow flicker up to a frequency of 100Hz (Williams, Mechler et al 2004; Logothetis, Murayama et al 2009) and the periphery is certainly more sensitive to high frequency flicker than the fovea (McKee and Taylor 1984; Tyler and Hamer 1990; Tyler and Hamer 1993; Horiguchi, Nakadomari et al 2009), the degree of entrainment is far higher when spatial contrast is present. Using a photocell and oscilloscope, we measured almost zero flicker in our LCD display below 100Hz during a mean field and we believe that it is unlikely that the small neural population that may be entrained (although not necessarily driven to spike more) above this frequency could drive the large offsets in BOLD signal that we observe.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that the parafovea may be more sensitive to the rapid flicker of our fluorescent monitor backlight. While some cells in macaque visual cortex can follow flicker up to a frequency of 100Hz (Williams, Mechler et al 2004; Logothetis, Murayama et al 2009) and the periphery is certainly more sensitive to high frequency flicker than the fovea (McKee and Taylor 1984; Tyler and Hamer 1990; Tyler and Hamer 1993; Horiguchi, Nakadomari et al 2009), the degree of entrainment is far higher when spatial contrast is present. Using a photocell and oscilloscope, we measured almost zero flicker in our LCD display below 100Hz during a mean field and we believe that it is unlikely that the small neural population that may be entrained (although not necessarily driven to spike more) above this frequency could drive the large offsets in BOLD signal that we observe.…”
Section: Discussionmentioning
confidence: 99%
“…These results seem to be consistent with the ''classical'' view of sustained and transient channels (a.k.a. the parvocellular vs. magnocellular processing pathways) with their different spatial frequency ranges (Hess & Snowden, 1992;Horiguchi et al, 2009;Keesey, 1972;Kulikowski & Tolhurst, 1973;Tolhurst, 1973Tolhurst, , 1975. In order to get good predictions of observers' ratings, it was necessary to have a multilinear regression that included both sustained and transient contributions.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis has it that, in the early stages of the visual system, there are two parallel pathways. The transient or magnocellular (M-cell) pathway acts primarily on low spatial frequencies while the sustained or parvocellular (Pcell) pathway acts primarily on middle and high spatial frequencies (Derrington & Lennie, 1984;Gouras, 1968;Hess & Snowden, 1992;Horiguchi, Nakadomari, Misaki, & Wandell, 2009;Keesey, 1972;Kulikowski & Tolhurst, 1973;Tolhurst, 1973Tolhurst, , 1975. The two pathways have been proposed to convey different perceptual information about temporal and spatial structure (Keesey, 1972;Kulikowski & Tolhurst, 1973;Tolhurst, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Uludag had shown that these transients are mostly positive and can be observed as sole response in a voxel or can overlap with positive or negative sustained responses. Based on the observation of sustained and phasic responses in the visual cortex, Horiguchi et al had suggested that there are two parallel temporal streams of visual processing (Horiguchi, Nakadomari, Misaki, & Wandell, 2009). Based on the observation of sustained and phasic responses in the visual cortex, Horiguchi et al had suggested that there are two parallel temporal streams of visual processing (Horiguchi, Nakadomari, Misaki, & Wandell, 2009).…”
Section: Other Transients: Onset and Offset Responses And Initial Ovementioning
confidence: 99%